Uruguay round outcome : agriculture july 1994 - Young, Elizabeth (Canberra : Department of Foreign Affairs and Trade, 1994)
In mercantilist economics the North was a big winner over the South at the Uruguay Round; in real economics an even bigger winner.
Also available in print.
Mode of access: World Wide Web.
Keywords: Agriculture -- Australia